2022
DOI: 10.1007/s00592-022-01984-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher odds of gestational diabetes among women with multiple pregnancies: a nationwide register-based cohort study in Finland

Abstract: Introduction The association between multiple pregnancies and the risk of gestational diabetes mellitus (GDM) has been moderately studied. The aim of this study is to evaluate whether women with multiple pregnancies are at a higher risk of developing GDM using nationwide high-quality registers. Materials and methods In this retrospective cohort study, data from the National Medical Birth Register (MBR) was used to evaluate the odds of GDM as a result of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The model was adjusted for covariates that were found to be risk factors for GDM based on the previous studies. The selected covariates included the following: maternal age, categorized maternal body mass index (BMI) using the WHO classification, maternal smoking status, IVF [ 4 ] and multiple pregnancies [ 5 ].…”
Section: Statisticsmentioning
confidence: 99%
“…The model was adjusted for covariates that were found to be risk factors for GDM based on the previous studies. The selected covariates included the following: maternal age, categorized maternal body mass index (BMI) using the WHO classification, maternal smoking status, IVF [ 4 ] and multiple pregnancies [ 5 ].…”
Section: Statisticsmentioning
confidence: 99%
“…The simultaneous growth of two fetuses may cause a greater degree of endocrine and metabolic changes, increasing the possibility of glucose metabolism disorders. 10 The current study has shown that fasting, OGTT1h, and OGTT2h blood glucose levels in women with twin pregnancies are higher than in those with singleton pregnancies, suggesting blood glucose levels during the second trimester of twin pregnancy is higher than that in a singleton pregnancy. In terms of the overall incidence of GDM, the incidence of GDM in 1985 cases of twin pregnancy included in this study was 21.01%, which is close to the 20.4% reported in a previous study conducted in China.…”
Section: Discussionmentioning
confidence: 47%
“…Confounding factors, such as higher maternal age and body mass index, gestational diabetes, and a higher proportion of instrumental vaginal deliveries (possibly requiring more pain relief in advance) among women with twin pregnancies might partly explain the higher proportion [13] , but the aORs still showed markedly increased odds for epidural analgesia among women with twin pregnancies. However, according to a recent study in Finland, women with gestational diabetes, to which women with twins are at higher risk [14] , had no higher proportion for labor analgesia [15] .…”
Section: Discussionmentioning
confidence: 98%
“…The utilization of the DAG approach aids in the selection of covariates to be incorporated into conventional statistical methods, thereby minimizing the potential bias in the resulting estimate [12] . The variables incorporated into the DAGs were selected by considering established risk factors and hypothesized causal pathways [13] , [14] , [15] , [16] , [17] . DAGitty automatically provides suggested sets of adjustment variables that may impact the primary outcome.…”
Section: Methodsmentioning
confidence: 99%